2020
DOI: 10.2196/15352
|View full text |Cite
|
Sign up to set email alerts
|

Online Health Resource Use by Individuals With Inflammatory Bowel Disease: Analysis Using the National Health Interview Survey

Abstract: Background The internet has enabled convenient and efficient health information searching which is valuable for individuals with chronic conditions requiring some level of self-management. However, there is little research evaluating what factors may impact the use of the internet for health-related tasks for specific clinical populations, such as individuals with inflammatory bowel diseases. Objective Our goal was to investigate the factors that influe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…For example, while the elderly could get more information online to improve their mental health, negative content can mislead them, damaging their mental health. Yin and Neyens (34) found that about 62.3% of those with inflammatory bowel diseases reported they had looked up health information online, 16.3% reported they had scheduled an appointment with a health care provider online, and 21.6% reported having used a computer to communicate with a health provider by email.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while the elderly could get more information online to improve their mental health, negative content can mislead them, damaging their mental health. Yin and Neyens (34) found that about 62.3% of those with inflammatory bowel diseases reported they had looked up health information online, 16.3% reported they had scheduled an appointment with a health care provider online, and 21.6% reported having used a computer to communicate with a health provider by email.…”
Section: Discussionmentioning
confidence: 99%
“…The data analysis was conducted in R version 4.1.2. A multivariate logistic regression model was built using the 'svyglm' function of the 'survey' package (Lumley & Scott, 2017), which takes into consideration of complex survey design and has been used in multiple studies (Cassy, Natário, & Martins, 2016;Ukwajunor, Akarawak, Abiala, & Adebayo, 2020;Yin & Neyens, 2020). The 'svyglm' function also enabled us to include the sample weights in order to generate a conclusion that can be generalized to the U.S. adult population.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuing recommendations should lead to the development of evidence-based explanations that help guide discussions with patients and introduce shared sensemaking and shared decision making into practice. These explanations should be easily adaptable to specific symptom presentations and different health literacy levels, and may potentially be supported by pamphlets, online resources, 43 and multidisciplinary care teams. 44 Explanations may be informed by what we already know from pain education.…”
Section: Implications For Future Research and Clinical Practicementioning
confidence: 99%